Determination of the Anti-Escherichial Activity of the Pyrimidine Derivative 3-[2-[(4,6-dimethylpyrimidin-2- yl)amino]-2-oxoethyl]quinazolin-4(3H)-one - A. A. Tsibizova; A. L. Yasenyavskaya; I. N. Tyurenkov; А. А. Ozerov; M. А. Samotrueva (Антибиотики и Химиотерапия)
The aim of this study was to investigate the antimicrobial activity of the pyrimidine derivative 3-[2-[(4,6-dimethylpyrimidin-2-yl)amino]-2-oxoethyl]quinazolin-4(3H)-one against Escherichia coli. The study of antimicrobial activity was carried out in vitro by serial dilutions of the pyrimidine compound, followed by determination of the minimum inhibitory concentration of 3-[2-[(4,6-dimethylpyrimidin-2-yl)amino]-2-oxoethyl]quinazolin-4(3n)-one (VMA-13-14) and in vivo on the model of generalized E.coli infection. The study of antimicrobial activity in vivo was carried out on 40 CBA mice weighing 19–20 g. All manipulations with animals were performed in accordance with the requirements of the regulatory documentation governing the maintenance of laboratory animals and work involving them. The antimicrobial activity of the pyrimidine compound 3-[2-[(4,6-dimethylpyrimidin-2-yl)amino]-2-oxoethyl]quinazolin-4(3H)-one against E.coli in vitro was evaluated in terms of mouse survival, contamination of blood and internal organs (liver, spleen, lungs, brain), as well as the total number of leukocytes and leukograms. The experiment determined that the pyrimidine compound 3-[2-[(4,6-di- methylpyrimidin-2-yl)amino]-2-oxoethyl]quinazolin-4(3n)-one demonstrates antimicrobial activity against E.coli: in vitro, it has a bactericidal effect at a concentration of 128 µg/ml; in vivo, it has an antimicrobial effect in conditions of generalized infection with the introduction of 50 mg/kg/day for 10 days. The antimicrobial effect of 3-[2-[(4,6-dimethylpyrimidin-2- yl)amino]-2-oxoethyl]quinazolin-4(3n)-one is comparable to ceftazidime, which is the drug of choice in the treatment of E.coli infection.